Development of the Operational Oceanographic System of Korea - Park, Kwang-Soon; Heo, Ki-Young; Jun, Kicheon; Kwon, Jae-Il; Kim, Jinah; Choi, Jin-Yong; Cho, Kyoung-Ho; Choi, Byoung-Ju; Seo, Seung-Nam; Kim, Young Ho; Kim, Sung-Dae; Yang, Chan-Su; et al. (Ocean science journal, 2015)
The Korea Operational Oceanographic System (KOOS) was developed at the Korea Institute of Ocean Science and Technology (KIOST) to produce real-time forecasting and simulation of interdisciplinary multi-scale oceanic fields. This offers valuable information to better mitigate coastal disasters, such as oil spills and other marine accidents, and provides the necessary ocean predictions to support the marine activities of government agencies, marine industries, and public users. The KOOS became operational in March 2012, and consists of several operational modules and realtime observations, including satellite remote sensing, coastal remote monitoring stations using high-frequency radar, and ocean observatories. The basic forecasting system includes weather, regional and high-resolution coastal circulation and wave prediction models; the practical application system includes storm surges, oil spills, and search and rescue prediction models. An integrated maritime port prediction system and data information and skill assessment systems are also part of the KOOS. In this work, the performance of the numerical models was evaluated by the skill assessment systems. From the monthly and yearly skill assessments, the models showed reasonable skill in predicting atmospheric and oceanic states except for the regional ocean circulation models. The ongoing development and improvement of the KOOS includes improvement of the model skills through the upgrade of the satellite-based sea surface temperature algorithm, the enhancement of the ocean monitoring ability, the upgrade of the forecasting models for higher spatial resolutions and the application of data assimilation techniques improved with the feedback from the skill assessment report.